1984
DOI: 10.2134/agronj1984.00021962007600010008x
|View full text |Cite
|
Sign up to set email alerts
|

Foxtail Barley Heading, Yield, and Quality as Influenced by Growth Regulators and a Desiccant1

Abstract: Foxtail barley (Hordeum jubatum L.) mixed with other forages harvested after heading or accumulated material bears awns that mechanically injure livestock and game animals upon consumption. This study examines the use of several growth regulators and a desiccant on supression of heading of foxtail barley and subsequent changes in forage yield and quality. During 1979 and 1981, stands of foxtail barley on two subirrigated, lowland sites (Ustic Torriflu· vent and Typic Ustifluvent soils) were treated at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…When foxtail barley matures, it produces stiff awns that can penetrate and become lodged in the mouth, eyes, ears, and skin of animals, commonly leading to infection, irritation, weight loss, and other debilitating injuries (Best et al 1978;Blouch 1953;Bowes 1984;Cords 1960). Forage quality and value of grasses grown for hay are also negatively affected by the presence of foxtail barley (White 1984). The adaptability and tolerance that foxtail barley exhibits in saline soils greatly exceeds that of many other pasture grasses and, therefore, explains its dominance in meadows, prairies, and pastures where salinity is a limiting factor (Badger and Ungar 1990;Dodd and Coupland 1966;Whitson et al 2000).…”
mentioning
confidence: 99%
“…When foxtail barley matures, it produces stiff awns that can penetrate and become lodged in the mouth, eyes, ears, and skin of animals, commonly leading to infection, irritation, weight loss, and other debilitating injuries (Best et al 1978;Blouch 1953;Bowes 1984;Cords 1960). Forage quality and value of grasses grown for hay are also negatively affected by the presence of foxtail barley (White 1984). The adaptability and tolerance that foxtail barley exhibits in saline soils greatly exceeds that of many other pasture grasses and, therefore, explains its dominance in meadows, prairies, and pastures where salinity is a limiting factor (Badger and Ungar 1990;Dodd and Coupland 1966;Whitson et al 2000).…”
mentioning
confidence: 99%
“…At the2-4 May application 90-95% of tillers had just initiated floral primordia. White (1984White ( , 1989 observed that, in foxtail barley and crested wheatgrass, reduction in seed head density was maximized when mefluidide was applied within 2 wk of floral differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have attributed this variability to the stage of plant morphological or floral development at application time (Gerrish and Dougherty 1983;Shaeffer and Marten 1986;White 1989). Reduction in seed head density was greatest in foxtail barley when mefluidide was applied within a week of floral primordia initiation (White 1984). In crested wheatgrass yield and seed head reductions, IVDOM and crude protein improvements were greatest when mefluidide applications (0.56 kg ha-') were made within 2 wk of the initiation of floral primordia (White 1989).…”
mentioning
confidence: 96%